(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
India has seen dramatic growth in tourism and slowly is emerging as one of the promising tourist destinations. However, the potential of the industry in terms of employment and income generation has not been fully utilized. An understanding of the tourist perception and the Brand equity a destination holds with its tourists enhances how the tourism industry in the country shapes up. The paper aims at contributing to the understanding of the key psychological factors that influence the formation of destination brand equity perceptions among tourists. The study has employed the Partial Least Square Structural Equation Modelling approach for validating the measurement and to estimate the effect of various antecedents on the Consumer Based Brand Equity in the context of India as a tourist destination.